2018
DOI: 10.1530/ec-18-0108
|View full text |Cite
|
Sign up to set email alerts
|

Depression in type 1 diabetes was associated with high levels of circulating galectin-3

Abstract: ObjectiveNeuroinflammatory responses are implicated in depression. The aim was to explore whether depression in patients with type 1 diabetes (T1D) was associated with high circulating galectin-3, controlling for metabolic variables, s-creatinine, life style factors, medication and cardiovascular complications.DesignCross-sectional.MethodsParticipants were T1D patients (n = 283, 56% men, age 18–59 years, diabetes duration ≥1 year). Depression was assessed by Hospital Anxiety and Depression Scale-depression sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 39 publications
0
65
1
Order By: Relevance
“…In these patients with T1D, we have previously shown that depression was associated with increased galectin-3 ( 23 ), a soluble β-galactoside-binding lectin, which is expressed in several cells such as activated macrophages and microglia, and is implicated in a variety of biological processes including neuroinflammation and neurodegeneration ( 24 , 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these patients with T1D, we have previously shown that depression was associated with increased galectin-3 ( 23 ), a soluble β-galactoside-binding lectin, which is expressed in several cells such as activated macrophages and microglia, and is implicated in a variety of biological processes including neuroinflammation and neurodegeneration ( 24 , 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The depressed patients did not exhibit lower levels of physical activity than the non-depressed [31] -as signs of lethargy -which is characteristic for atypical depression [5]. We have also shown in these patients with T1D that high levels of galectin-3 [32] and HbA1c [33], and low levels of HDL-cholesterol were associated with depression [31].…”
Section: Introductionmentioning
confidence: 55%
“…In the further analyses we chose to define low sTWEAK as levels below the 70 th percentile, as this definition of low sTWEAK showed the highest association with depression. We have previously performed the same procedure for galectin-3 which showed that galectin-3 levels above the 85 th percentile showed the highest association with depression [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations